HUBUNGAN ANTARA PERSEPSI TERHADAP KUALITAS PELAYANANWISATA DENGAN LOYALITAS PENGUNJUNG WISATA GROJOGAN SEWU TAWANGMANGU - Qoyyumi, Annisa Nurul; Janah, Maslichah Raichatul (TALENTA, 2014)
Tourism is one sector which is considered to have the ability to donate the largest foreign exchange after oilÂ  and gas . Tourism activities provide advantages and benefits for a country / region tourist destination , although not apart any losses and the resulting negative impact , especially on the culture and the environment . The purpose of this study are to determine ; 1 ) the relationship between perceptions of service quality and loyalty visitor attractions ; 2 ) the role or effective contribution to the perception of service quality and loyalty visitor attractions . The hypothesis proposed a positive relationship between perceptions of service quality dimensionswith loyalty visitor attractions . Subjects in this study were visitors Nature ParkGrojogan Sewu Tawangmangu Karanganyar Central Java , amounting to 146 people . Sampling technique in this study is incidental non-random sampling . Measuring instruments used in this study are scaled visitor loyalty and perceptions of service quality scale . Â Based on the calculation results of the analysis techniques obtained Pearson product moment correlation coefficient ( r) of 0.327 ; p = 0.000 ( p < 0.01 ) means that there is a significant positive relationship between perceptions of service quality and visitor loyalty . The role of perception or effective contribution to the quality of service to visitors sebesar10,7 % loyalty shown by the determinant coefficient ( r2 ) of 0.107 . 89.3 % means that there are other variables that affect the loyalty of visitors outside variables such as perception of the quality of service objectof the visit , imagery , socioeconomic status and condition of natural factors . Based on the results of the categorization of unknown variable perceptions of service quality has the empirical mean ( RE ) of 96.068 and the mean hypothetical ( RH ) of 82.5 , which means the perception of service quality is high on the subject . Variables known to the average visitor loyalty empirical ( RE ) of 69.178 and the mean hypothetical ( RH ) of 70 which means the visitor loyalty research subjects classified as moderate . Based on the results of the final model of the stepwise analysis note that the perception of the quality of service aspects are the most dominant contributing effectively to the loyalty of visitors are aspects of Empathy ( X4 ) of 13,374 % . The results showed no significant positive relationship between perceptions of service quality and visitor loyalty . This means that a variable perception of service quality include aspects in it can be used as a predictor to predict or measure loyalty visitors .